Zabawy dzieci ziemiańskich w drugiej połowie XIX i na początku wieku XX w świetle pamiętnikarstwa - Nawrot-Borowska, Monika (Biuletyn Historii Wychowania, 2013)
Games of landowning children in the in the second half of XIXth and at the beginning of XXth century in the light of the memories. The aim of this article is to show the playground of children from landowning families during the second half of the nineteenth and the early twentieth century. An attempt was made to present the playgrounds of wealthy children, their characteristics, space, and also to determine the place and role of play in the lives of children of landowners. The types of games for children, both boys and girls have been presented. Also children’s toys were made the subject of research. The conclusions presented have been based entirely on the analyses of diaries, memoirs and biographies of the representatives of landowning class.